Numerical Investigation of Turbulent Natural Convection for a Cavity Having Sinusoidal Protuberances on a Vertical Wall - K Rahmani (Journal of Applied Fluid Mechanics, 2013)
This work concerns the study of heat transfer by means of natural convection with fluids circulating in enclosures. These topics are largely studied both experimentally and numerically due to their wide industrial application in various fields such as nuclear energy, the heating and cooling of buildings, solar collectors, etc. A great deal of relevant research work consists in numerical simulations of natural convection mechanisms with laminar flows in closed cavities. In this context, the present study comes as a contribution in numerical form investigating the turbulent natural convection in vertical enclosure which presents sinusoidal protuberances on one of its vertical walls. Both the top and bottom of the enclosure are open to allow the fluid flow. The horizontal walls are supposed adiabatic. We are interested in determining for various amplitudes and periods. The influence of geometry on several factors such as: temperature, the number of local Nusselt, the turbulent kinetic energy k and its dissipationï¥. Based on the Navier-Stokes equations and Boussinesq approximation, the equations were solved by the CFD technique using the Finite Volume Method In the case of enclosures having the form ratio equal to 0.6 (A=0.6). Given the steady conditions of heat flow on the vertical walls and the pressures at the entry and exit of the cavity, the results show that when we gradually increase the amplitudes of the protuberance wall (say a=0.005 m, a=0.010, a=0.015, a= 0.02, and a=0.025), the maximal temperature increases with the increase of amplitude. This is due to the rise of the heat transfer surface of the modified wall. Regarding heat transfer parameters, the results show that the number of local Nusselt varies relatively with the amplitudes. This explains that the modified wall is affected locally by a pure conduction. The results obtained in this study are in agreement with recent works of several authors.